Status and Prospects of Botanical Biopesticides in Europe and Mediterranean Countries - Acheuk, Fatma; Basiouni, Shereen; Shehata, Awad A.; Dick, Katie; Hajri, Haifa; Lasram, Salma; Ntougias, Spyridon (Mdpi, 2022)
Concerning human and environmental health, safe alternatives to synthetic pesticides are urgently needed. Many of the currently used synthetic pesticides are not authorized for application in organic agriculture. In addition, the developed resistances of various pests against classical pesticides necessitate the urgent demand for efficient and safe products with novel modes of action. Botanical pesticides are assumed to be effective against various crop pests, and they are easily biodegradable and available in high quantities and at a reasonable cost. Many of them may act by diverse yet unexplored mechanisms of action. It is therefore surprising that only few plant species have been developed for commercial usage as biopesticides. This article reviews the status of botanical pesticides, especially in Europe and Mediterranean countries, deepening their active principles and mechanisms of action. Moreover, some constraints and challenges in the development of novel biopesticides are highlighted.
Keywords: botanical insecticides; botanical herbicides; botanical fungicides; Mediterranean region; bioactive substances; mechanism of action